Neurovascular complications after supracondylar humerus fractures in children. (April 2017) - Leiblein, Maximilian; Lustenberger, Thomas; Schulz, Anne-Kathrin; Schmitz-Rixen, Thomas; Marzi, Ingo
Abstract: Background: Supracondylar fractures of the humerus are a common injury in pediatric traumatology. The most common operative therapy is closed reduction and percutaneous pinning using K-wires. Common complications associated with this entity are neurovascular lesions, especially of the brachial artery and the median nerve. Methods: We report two cases of patients treated in our trauma-center with supracondylar fracture of the humerus (AO IV°) and neurovascular complications. Results: Both patients underwent open revision and recovered completely in their further course. Conclusion: We recommend detailed neurovascular examination initially and after reposition of the fracture. The threshold for open reduction in cases of irreducible fractures should be low. In the presence of neurovascular impairment an open revision is mandatory, even months after the initial Trauma. Level of evidence: Level V (case report).